Community Centered Mitigation Based on Science Literature to Reduce The Risk of Disaster in Indonesia - Supartono, Basuki; Ambari, Muhamad DJazuli; Rudi, Muhamad (Bulan Sabit Merah Indonesia, 2022)
Disasters are a potential threat to the lives of the Indonesian people. The trend of disasters in Indonesia is increasing regarding the number, type, impact, and complexity of the problem. All of that burdens individuals, communities, nations, and countries. Reducing this burden remains a common challenge. A simple activity to reduce the burden is to carry out risk reduction and disaster mitigation activities involving various stakeholders. Community-based mitigation activities utilizing science literacy can be an alternative model of solutions to overcome this.